Epistasis in neurotransmitter receptors linked to posttraumatic stress disorder and major depressive disorder comorbidity in traumatized Chinese - Xu, Ling; Zhang, Jingyi; Yang, Haibo; Cao, Chengqi; Fang, Ruojiao; Liu, Ping; Luo, Shu; Wang, Binbin; Zhang, Kunlin; Wang, Li (Frontiers in Psychiatry, 2024)
Background: Posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) comorbidity occurs through exposure to trauma with genetic susceptibility.Neuropeptide-Y (NPY) and dopamine are neurotransmitters associated with anxiety and stress-related psychiatry through receptors. We attempted to explore the genetic association between two neurotransmitter receptor systems and the comorbidity of PTSD-MDD comorbidity.Methods: Four groups were identified using latent profile analysis (LPA) to examine patterns of PTSD and MDD comorbidity among survivors who exposure to earthquake-related trauma: low symptoms, predominantly depression, predominantly PTSD, and PTSD-MDD comorbidity. NPY2R (rs4425326), NPY5R (rs11724320), DRD2 (rs1079597), and DRD3 (rs6280) were genotyped from 1140 Chinese participants exposed to earthquake-related trauma. Main, gene-environment interaction (G × E) and gene-gene interaction (G × G) effects for low symptoms, predominantly depression, and predominantly PTSD, were tested using a multinomial logistic model with PTSD-MDD comorbidity as a reference.Results: The results demonstrated that compared to PTSD-MDD comorbidity, epistasis (G × G) NPY2R-DRD2 (rs4425326 × rs1079597) affects low symptoms (β = -0.66, OR = 0.52 [95% CI: 0.32-0.84], p = 0.008, pperm = 0.008) and predominantly PTSD (β = -0.56, OR = 0.57 [95% CI: 0.34-0.97], p = 0.037, pperm = 0.039). While NPY2R-DRD3 (rs4425326 × rs6280) impacts low symptoms (β = 0.82, OR = 2.27 [95% CI: 1.26-4.10], p = 0.006, pperm = 0.005) and predominantly depression (β = 1.08, OR = 2.95 [95% CI: 1.55-5.62], p = 0.001, pperm = 0.001). The two G × G effects are independent. Conclusions: NPY and dopamine receptor genes are related to the genetic etiology of PTSD-MDD comorbidity, whose specific mechanisms can be studied at a multi-level.